The Concept of A Perfect BUMDES Law Entity After Law No. 11/2020 on Working Creation in The Role of Increasing Village Income - Muhammad Ikhsan Kamil; Sukarno; Khairul Aswadi; Rauzi, Fathur (Jurnal IUS Kajian Hukum dan Keadilan, 2023)
BUMdes is a productive forum in encouraging the empowerment of economic potential in the village, in addition to its existence will be able to open up employment opportunities. This indicates that good management construction is also needed, a construction that supports efficiency so that the principle of independence in village development is realized. The priority of BUMdes is on economic benefits, in addition to social benefits, but the legal aspect must be a foothold. Not merely pursuing benefits just because of the new spirit. However, it is necessary to know the rules to understand the construction as well as the alternatives in it. Regulatory incompleteness (norm ambiguity), namely that based on Government Regulation Number 11 of 2021 concerning Village-Owned Enterprises, BUMdes is in the form of a legal entity, which in its explanation cannot be equated with PT and Cooperatives, while in terms of regulation, business entities can take the form of PT legal entities (Law Number 40 of 2007 concerning Limited Liability Companies). The purpose of this study is to analyze the BUMdes institutional model as a legal entity in Indonesia to increase village income. The method used in this research is normative legal research with statutory, conceptual, and philosophical approaches. The results of the study confirm that BUMdes has a goal as stated in the definition of BUMdes that BUMdes not only aims to increase Village PAD but also must prosper the Village Community itself so that the Legal Entity Form of BUMdes after work creation must be regulated so that it aims directly at the welfare of the village community.